Hubungan Perilaku Sarapan Pagi Dan Kualitas Tidur Dengan Konsentrasi Belajar Siswa SMA Negeri 88 Jakarta Timur Tahun 2023 - Khailanisa, Aulya; Linda, Ony (LPPM Sekolah Tinggi Ilmu Kesehatan Pekanbaru Medical Center, 2023)
Learning concentration is needed in any learning process. If students cannot concentrate on the ongoing lesson, then the impact will be detrimental to the students themselves because they do not get anything from the lesson. The purpose of this study was to determine the relationship between breakfast behavior and sleep quality with the concentration of learning of SMA Negeri 88 Jakarta students. This study uses quantitative analytics with a Cross Sectional research design. The sampling technique used in this study was simple random sampling with a total of 146 people. The analysis of this study used univariate and bivariate analysis using the Chi Square statistical test. Univariate results showed that 68.8% of students concentrated on learning well, 82.9% of students had breakfast behavior and 65.8% of students had good sleep quality. Bivariate test results show there is a relationship between breakfast behavior (Pvalue = 0.000) and there is a relationship between sleep quality and learning concentration (Pvalue = 0.000)